Protective effect of different antioxidant agents in UVB-irradiated keratinocytes - Sara Salucci; Sabrina Burattini; Francesca Buontempo; Alberto Maria Martelli; Elisabetta Falcieri; Michela Battistelli (European Journal of Histochemistry, 2017)
Skin cells can respond to UVB-induced damage either by tolerating it, or restoring it through antioxidant activation and DNA repair mechanisms or, ultimately, undergoing programmed cell death, when damage is massive. Nutritional factors, in particular, food antioxidants, have attracted much interest because of their potential use in new preventive, protective, and therapeutic strategies for chronic degenerative diseases, including skin inflammation and cancer. Some polyphenols, present in virgin olive oil, well tolerated by organism after oral administration, show a variety of pharmacological and clinical benefits such as anti-oxidant, anti-cancer, anti-inflammatory, and neuro-protective activities. Here, the protective effects of antioxidant compounds against UV-induced apoptosis have been described in HaCat cell line. Human keratinocytes were pre-treated with antioxidants before UVB exposure and their effects have been evaluated by means of ultrastructural analyses. After UVB radiation, a known cell death trigger, typical apoptotic features, absent in control condition and in antioxidant alone-treated cells, appear. An evident numerical decrease of ultrastructural apoptotic patterns and TUNEL positive nuclei can be observed when natural antioxidants were supplied before cell death induction. These data have been confirmed by molecular investigation of caspase activity. In conclusion, this paper highlights antioxidant compound ability to prevent apoptotic cell death in human keratinocytes exposed to UVB, suggesting, for these molecules, a potential role in preventing skin damage.